RARE INNATE ANOMALY OF INTRATHORACIC POSITION OF HEART - Lyahovskiy, V.I.; Сакевич, Р.П.; Demyanuk, D.G.; Пузирьов, Г.С.; Hanenko, E.B.; Ryabushko, R.N. (World of Medicine and Biology, 2012)
We enlarge a clinical observation of 79 years old patient where we discovered ischemic heart disease, acute transmural myocardial infarction of the back wall that was spread to the apex-septal zone, with a full complicated a-v blockade and acute attack of Morgagni-Adams-Stokes syndrome. It was impossible to perform temporal cardio-stimulation so we decided to make an urgent implantation of permanent artificial pacemaker (APM). The anomaly of heart location was suspected during this operation. Not typical position of the heart was shown on cavography. The trunk of v. cava superior together with the right section of the heart was in the far left position. The aorta was located to the right. There was a turn of cardiovascular structures from right to left in 180°. There was no disposition of abdominal organs. Such a disposition of heart was considered as left-formed left-located heart.